Investigation of pyrimidine nucleoside analogues as chemical probes to assess compound effects on the proliferation of Trypanosoma cruzi intracellular parasites - Sykes, Melissa Louise; Hilko, David Hugh; Kung, Livia Isabella; Poulsen, Sally-Ann; Avery, Vicky Marie (PLOS Neglected Tropical Diseases, 2020)
Author summary Chagas disease occurs within 21 countries in the Americas, causes over 10, 000 deaths per year and a further 25 million people are at risk of being infected. The cause of Chagas disease is Trypanosoma cruzi, a single celled protozoan parasite, which enters the bloodstream of a host by the bite of a “kissing bug”. In advanced disease stages, the parasite hides in heart and gut tissue and is difficult to treat. Identifying the replicative ability of these parasites is important to understanding Chagas disease progression and the effectiveness of compounds and drugs for treatment. By testing a panel of nucleoside analogues that may incorporate into DNA during synthesis, we developed an image-based method with a fluorescently-labelled DNA probe to identify replicating parasites. This method has effectively shown that drugs used to treat the parasite are able to clear intracellular infection, whilst a compound that was not efficacious in clinical trials leaves replicating T. cruzi behind. This methodology can be used to understand the action of further compounds and supports the identification of new, less toxic probes to assess intracellular parasite replication.